Evaluating the Impact of Electronic Prescribing on Medication Administration - Monira Miah; Ivan Shanley; Stephanie Ko; Vanessa Jacobs (BJPsych Open)
Aims: With the introduction of electronic prescribing (EP) to an older adult inpatient psychiatric ward after many years of paper charts, it was anticipated that unfamiliarity with the system would disrupt medication administration. This study sought to quantify that. The measure of disruption was defined as the deviation between the time of prescribed administration and the time medication was actually given.